On the interpretation of giving, taking and destruction in dictator games and joy-of-destruction games - Zhang, Lyla; Ortmann, A. (University of New South Wales, 2013)
The literature on dictator [D] and joy-of-destruction [JoD] games demonstrates that people can be nice and nasty. We study, by way of an experiment with between-subjects and within-subjects features, to what extent behaviors are context dependent and consistent. We find that, for one-shot D and JoD games, our participants' niceness and nastiness depend on the choice set. Contradicting the observed altruism and nastiness, participants tend to be selfish but nonetheless make choices that increase social welfare when given the opportunity.